CASCADED SQUARE LOOP BANDPASS FILTER WITH TRANSMISSION ZEROS FOR LONG TERM EVOLUTION (LTE) - Iis Andini; Dian Widi Astuti; Muslim Muslim (Universitas Mercu Buana, 2018)
In this paper, we present a bandpass filter that passed frequency of 1.7 GHz – 1.8 GHz. It is applied for an uplink frequency in 4G 1800MHz. This filter is created by using substrate PCB TMM-10i and has a compact size of 42 mm x 42 mm. The compact size is also important besides selectivity. The selectivity is achieved by implementing cascade square loop resonator method which generated transmission zeros. Actually, transmission zeros are obtained from the coupled resonator. The bandpass filter is designed by adding an external resonator on each square of the resonator loop and a patch to the inside of the square loop resonator. The parameter performances are simulated by HFSS. The parameter performances for return loss value is 14.24 dB at frequency 1.75 GHz and insertion loss value is 0.65 dB at frequency 1.75 GHz. By using VNA Anritsu MS 2026A, prototype bandpass filter is measured. The measurement results for return loss value is 6.8 dB and insertion loss value is 2.2 dB.